PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA WORDWALL TERHADAP HASI BELAJAR PENDIDIKAN PANCASILA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study was low the learning outcomes in Pancasila Education class V at SDN 1 Margoyoso. This study aims to determine the effect of using Problem Based Learning assisted by Wordwall on learning outcomes. The method used in this research is quasi- experimental desaign with a quantitative approach. The population amounted to 43 students, a sample of 23 students using purposive sampling technique. Data collection techniques were carried out through documentation and tests. Analysis of research data using simple linear regression. The result of the study is that there is a which that there is a positive and significant influence between the use of the Problem Based Learning model assisted by Wordwall on the learning outcomes of students in grade V Pancasila Education at SDN 1 Margoyoso.